2021
DOI: 10.1021/acsfoodscitech.1c00254
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Analytical Detection of Olive Oil Adulteration

Abstract: Olive oil is a popular food ingredient worldwide. Detecting economically motivated adulteration of olive oil is important to protect consumers’ interest. This review highlights the recent developments of analytical techniques in authentication and detecting adulteration of olive oils. The major characteristics and performances of chromatographic, spectroscopic, and other techniques were summarized. This work may provide a useful perspective toward future industrial applications for the quality assurance of oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…It can be observed that bands around 350-380 nm correspond to the highest absorbers for the emissions of free fatty acids, vitamins, phenolic compounds, and oxidation products, and the bands around 405 and 500 nm are related to the absorption of carotenoids, chlorophylls, and pheophytin. Considering the emission band registered between 400 and 600 nm, similar spectra have been recorded by other authors in refined vegetable oils, which relate this region to the emission of tocopherols (vitamin E), flavins, and their derivatives (vitamins from the B complex), and oxidation products such as hydroperoxides and free fatty acids [24,28,38,[41][42][43][44][45][46].…”
Section: Steady-statesupporting
confidence: 79%
See 2 more Smart Citations
“…It can be observed that bands around 350-380 nm correspond to the highest absorbers for the emissions of free fatty acids, vitamins, phenolic compounds, and oxidation products, and the bands around 405 and 500 nm are related to the absorption of carotenoids, chlorophylls, and pheophytin. Considering the emission band registered between 400 and 600 nm, similar spectra have been recorded by other authors in refined vegetable oils, which relate this region to the emission of tocopherols (vitamin E), flavins, and their derivatives (vitamins from the B complex), and oxidation products such as hydroperoxides and free fatty acids [24,28,38,[41][42][43][44][45][46].…”
Section: Steady-statesupporting
confidence: 79%
“…Considering the emission band registered between 400 and 600 nm, similar spectra have been recorded by other authors in refined vegetable oils, which relate this region to the emission of tocopherols (vitamin E), flavins, and their derivatives (vitamins from the B complex), and oxidation products such as hydroperoxides and free fatty acids [24,28,38,[41][42][43][44][45][46].…”
Section: Steady-statesupporting
confidence: 79%
See 1 more Smart Citation
“…The most frequent adulteration of olive oil involves blending with less expensive and readily available vegetable/seed oils. The assessment of olive oil authenticity is an extremely important and challenging process aimed at protecting consumers and producers and, therefore, is the focus of intensive research efforts . The challenge has two aspects: (a) determining whether the olive oil sample is adulterated and (b) identifying the added vegetable oil.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid analysis is practically unfeasible with MIR microscopes based on a glow bar source. This is also a novel combination of MIR spectroscopy and multivariate analysis in the field of food analysis. This combination is more often seen to be employed in a classification or a multivariate model-based assay role. …”
Section: Introductionmentioning
confidence: 99%